Meningkatkan Kompetensi Pembimbing Dan Penyuluh Melalui Profesionalitas Di Satuan Pendidikan Formal Non-Formal - Adinda, Fatima; Azahra, Sevina; Rahmayanti, Adisti Aisyah; Zahra, Dliya Lahuda; Karwati, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Abstract. Understanding the Competence of Mentors and Instructors to Increase Professionalism in the Implementation of Formal and Non-formal Education Units. There are still many tutors and instructors who currently do not have sufficient competence to answer or even be the right solution to the needs that have been determined. This can have a negative impact on the quality of education provided covering various important aspects, such as program planning, program implementation, communication, understanding individual behavior, maintaining professionalism, and evaluation. This research aims to find out how supervisors and instructors can have good professional competence to be more effective in delivering learning material, facilitating interaction between targets (students/learning residents), as well as improving the quality of learning and teaching. This research method uses the type of research method used, namely research using data collection using the library study method, namely in the form of literature studies that are appropriate to the research, both in the form of book sources and internet sources.